1995
DOI: 10.1002/jctb.280620412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluid rheological properties on mass transfer in a bioreactor

Abstract: Rheological properties and oxygen mass transfer coefficient (kL a) were investigated in a stirred reactor (10 dm3) in the course of fermentations producing microbial polysaccharides—pullulan and xanthan. The fermentation broths behaved as pseudoplastic non‐Newtonian fluids in both cases. Studies on the relationship between fluid rheological properties and kL a were also carried out. The oxygen mass transfer coefficient decreases during the fermentation and exponential equations have been obtained to describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Thus, the conventional method of oxygen supply is inadequate for this cultivation. It should be noted that the bioreactor k L a for the conditions employed in the conventional cultivation was 28.8 h −1 , which compares well with 21.6 h −1 , obtained at a higher rpm (450 rpm), in another stirred tank used for xanthan gum studies reported in the literature (Li et al, 1995). Thus, the k L a employed was a reasonable value.…”
Section: Inadequacy Of Aerationsupporting
confidence: 78%
“…Thus, the conventional method of oxygen supply is inadequate for this cultivation. It should be noted that the bioreactor k L a for the conditions employed in the conventional cultivation was 28.8 h −1 , which compares well with 21.6 h −1 , obtained at a higher rpm (450 rpm), in another stirred tank used for xanthan gum studies reported in the literature (Li et al, 1995). Thus, the k L a employed was a reasonable value.…”
Section: Inadequacy Of Aerationsupporting
confidence: 78%
“…There could not be a proper correlation drawn with viscosity until first 6 h, but later an increase in viscosity contributed towards decrease in k L a by offering oxygen transfer resistance. These results were in direct concordance with the microbial production of polysaccharides where the increase in viscosity decreased k L a by decreasing gasliquid specific surface area [21].…”
Section: Th Sludge Without Tween 80supporting
confidence: 68%
“…Similar observations can be made for the properties needed to precisely predict transport of metabolites, nutrients, or CO 2 . So far, most studies are based on experimental investigations, which are usually interpreted with simple theoretical models 3, 4, 8–11. First‐principles methods to predict mass‐transfer coefficients, transport rates, and other parameters in non‐Newtonian fluids have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%